2012
DOI: 10.1177/1049732312468063
|View full text |Cite
|
Sign up to set email alerts
|

Children and Youth With Disabilities

Abstract: There is a paucity of explicit literature outlining methods for single-interview studies with children, and almost none have focused on engaging children with disabilities. Drawing from a pilot study, we address these gaps by describing innovative techniques, strategies, and methods for engaging children and youth with disabilities in a single qualitative interview. In the study, we explored the beliefs, assumptions, and experiences of children and youth with cerebral palsy and their parents regarding the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…However, it is possible that teachers' expectations at the beginning of the study period aligned with actual student attention and behavior, and both measures did actually improve over the course of the outdoor sessions with more exposure to outdoor EE. This third explanation aligns with past research on the effects of green space on students with ECBD, which suggests that time outdoors can improve attention and reduce hyperactivity (Ruiz-Gallardo et al, 2013;Amoly et al, 2014;Flouri et al, 2014;Moore et al, 2016;Kuo et al, 2018). Our qualitative results show some evidence of each of these explanations, as some teachers expressed surprise at how engaged ECBD students were outdoors; others seemed to transform how they viewed behavior as appropriate or not; and others reported changes in the students themselves.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it is possible that teachers' expectations at the beginning of the study period aligned with actual student attention and behavior, and both measures did actually improve over the course of the outdoor sessions with more exposure to outdoor EE. This third explanation aligns with past research on the effects of green space on students with ECBD, which suggests that time outdoors can improve attention and reduce hyperactivity (Ruiz-Gallardo et al, 2013;Amoly et al, 2014;Flouri et al, 2014;Moore et al, 2016;Kuo et al, 2018). Our qualitative results show some evidence of each of these explanations, as some teachers expressed surprise at how engaged ECBD students were outdoors; others seemed to transform how they viewed behavior as appropriate or not; and others reported changes in the students themselves.…”
Section: Discussionsupporting
confidence: 87%
“…A 6-year analysis revealed that the intervention led to a significant decrease in dropout rates, a significant increase in classes passed, and an increase in overall behavior and attitude (Ruiz-Gallardo et al, 2013). In a study by Moore et al (2016), experienced EE practitioners took a class of students on an experiential nature hike where they used technology to engage with the outdoors. Researchers conducted additional interviews and observations of two students with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Children selected the space, the aspects they found important in managing the disease, and they felt more comfortable [24] , giving them some sense of control during the interview [6] . As in previous reports [10,14,25] , they were able to tell past and current stories, as well as different situations in fun and meaningful ways [25,26] .…”
Section: Advantages Of Using Puppetsmentioning
confidence: 63%
“…Then, the interviewer and child(ren) read the information letter and informed consent together before the child signed. The interviewer explained among others that the child could opt out any time without reason, did not have to answer questions he or she did not want to answer, and could ask questions to the interviewer-practiced with a starting game (Teachman & Gibson, 2013).…”
Section: Ethicsmentioning
confidence: 99%
“…The child and interviewer asked each other these questions to practice interviewing, get to know each other, and diminish power differentials by explaining there were no "right" or "wrong" answers and enabling the child to ask the interviewer (personal) questions (Teachman & Gibson, 2013). In order to facilitate reflection and tailor the interview to each respondent, a toolkit with customizable interview techniques was developed (Teachman & Gibson, 2013). This contained creative methodologies like vignettes, sentence starters, and a ranking exercise with weight-related words.…”
Section: Data Collectionmentioning
confidence: 99%